Antipassive structure in Tenetehára (Tupi-Guarani family) - Duarte, Fábio Bonfim; Camargos, Quesler Fagundes; Castro, Ricardo Campos de (Revista Brasileira de Linguística Antropológica, 2017)
This article aims to describe and examine the antipassive construction in the Tenetehára language (Tupi-Guarani family). For this, it will be shown that the transitive verbs, on receiving the morpheme {puru-}, then exhibit the following properties of antipassive constructions: (i) they come to have an intransitive syntactic structure and (ii) the abstract Case of the internal argument is not valued by v, but by the postposition -ehe. Generally, such configurations behave essentially like intransitive sentences. Using a minimalist approach, we show that the main difference between an antipassive clause and a transitive one is that although the antipassive vP selects an external argument, its head is not able to value the abstract Case of the internal argument. For this reason, the object is dependent on the postposition -ehe for the oblique Case. Furthermore, unlike what happens in the derivation of transitive constructions, the Ï†-feature of the antipassive vP is lexically valued, which does not allow the agreement (nominative system) in terms of Ï†-feature, with its external argument. The result is that this external argument moves to the highest vP Spec position in the tree structure, whose head is instantiated by the verb {-wer} “want”, with which it establishes a relationship agreement in terms of Ï†-feature , triggering the second agreement paradigm (absolutive system).